Dividing between 'us' and 'them': the framing of gender and sexuality by online followers of the Dutch populist radical right. (1st September 2021) - Fiers, Ruud; Muis, Jasper
Abstract : This article investigates the ways in which online followers of the Dutch populist radical right discuss gender and sexuality. Analysing comments on the Facebook pages of the Party for Freedom and Forum for Democracy, we show that they use these issues to pit 'us' against 'them' – groups that are defined differently, depending on the context. Women's emancipation and gay acceptance are defended and used to divide 'civilised' Dutch and 'backward' immigrants. This 'liberal' immigration critique is especially characteristic of Party for Freedom followers. Other progressive causes, such as transgender rights and feminism more broadly, are framed as elite projects, out of touch with 'ordinary people'. This backlash standpoint is more often articulated by Forum for Democracy followers.